Estrutura da vegetação natural e caracterização de árvores matrizes e frutos de mangabeira (hancornia speciosa gomes) no maranhão - Silva, Larissa de Paula Viana da (2016)
The unknown potential of natural áreas of Hancornia speciosa Gomes in the Northeast have high risks of extinction of species and contributed to its underutilization. Little is known about the general aspects of fruit tree in their naturally occurring environments. The labor goals were to characterize the structure of the remaining vegetation of mangabeira and select and characterize morphologically mangabeiras arrays and physico-chemically of their fruits. The study was conducted in the villages Patizal, Recanto and Recurso, Morros, MA, whose floristic composition was determined by the quadrant method. They selected one adult and one regenerant per quadrant. The phytosociological parameters determined were: density, frequency and relative dominance, Importance value (IV) e Coverage value (CV), Shannon and Weaver´s Diversity Index (H‟) and Sorensen´s Similarity Index (SSI). In the sample areas were selected arrays 45 of which were measured the total height, stem height, diameter, canopy volume, number of main and secondary branches and number of fruits. Were collected 20 fruits per array and were determined the mass, length and diameter of the fruits, pulp mass more peel, pulp yield, number and seed mass, pH, acidity and soluble solids. For all the phytosociological parameters H. speciosa reached relevant position with importance value varying 25.15% to 29.38% (regenerant stratum) and 29% to 56.64% (adult stratum) between the three sampled áreas. There was a high degree of variability for all variables studied except for the pulp yield (average of 86.69%, minimum of 76.75% and maximum of 91.11%, CV% 3.51). Highlights the positive and significant correlations of high magnitude of mass variables of fruit and pulp mass more peel with the number of seeds